Awareness and practices of correct and consistent use of condoms among sexually active males in India - a cross sectional study - Majra, Jai Pal; Silan, Vijay Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: About 2.5 million Indian are estimated to be HIV positive apart from the other STIs and around 1/4th of the births are unwanted. Condom has become a popular method being promoted for meeting these challenges. The objectives of the study were to understand the awareness and practices regarding correct and consistent use of condoms among sexually active males in India. Methods: Three randomly selected primary health centers in southern India. All male members reported to be using condoms by the PHCs, were visited at their homes. A pre-tested check list (Yes/No) type questionnaire was used to collect the data. Commonly available guide line regarding correct and consistent were used as the baseline knowledge. Responses thus received were evaluated and graded using five point scales. Income, education and years of use wise differentials were also analyzed. Results: Out of 7326 eligible couples 7.2% were reported to be using condoms. Response rate was 88 percent. 27 (12%), 82 (36%), 89 (39%), 18 (8%) and 11 (5%), were having poor, fair, good, very good and excellent level of awareness respectively and fewer were putting their knowledge into practice. Respondent having schooling for more than ten years or per capita income of more than Rupee 1000 or using condoms since more than five years were having better level of awareness as well as practices. Conclusions: Awareness and practices regarding correct and consistent condom use lags substantially behind the desired levels.